2008
DOI: 10.1093/ajcn/88.2.364
|View full text |Cite
|
Sign up to set email alerts
|

Age-appropriate body mass index in children with achondroplasia: interpretation in relation to indexes of height

Abstract: Background: Achondroplasia is the most common short stature skeletal dysplasia, with an estimated worldwide prevalence of 250 000. Body mass index (BMI)-for-age references are required for weight management guidance for children with achondroplasia, whose body proportions are unlike those of the average stature population. Objective: This study used weight and height data in a clinical setting to derive smoothed BMI-for-age percentile curves for children with achondroplasia and explored the relation of BMI wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Obesity and high BMI are frequently reported in achondroplasia . However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and high BMI are frequently reported in achondroplasia . However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and high BMI are frequently reported in achondroplasia. 18,22,32,[60][61][62][63] However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, 64 and even more in individuals of disproportionate short stature, such as achondroplasia. 32,60,65 In a recently published paper, the authors found an atypical obesity with preferential abdominal obesity in achondroplasia children.…”
Section: Medical Complications Health Characteristics and Psychosomentioning
confidence: 99%
“…15 Although high BMI has long been thought to be protective for bone mass, the relationship between BMI and osteopenic conditions has been inconclusive, with conflicting findings. Fasolino and Whitright reported lower BMI with high rates of osteopenia and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Specific growth standards for genetic disorders have been prepared for children in ACH, Turner Syndrome and other conditions [8,[10][11][12][13]31]. They are useful not only for detecting additional conditions which could affect growth, but also for estimating final height and hence evaluating the impact of growth-promoting treatments [22,31].…”
Section: Introductionmentioning
confidence: 99%